ETIKA KOMUNIKASI BISNIS ONLINE DI ERA NEW NORMAL PERSPEKTIF HUKUM BISNIS ISLAM - Dewi Arianti, Hawari Muhammad (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2021)
This article aims to determine the ethics of online business communication from the perspective of Islamic law. The research method used in this study is library research (library research) with a philosophical juridical approach, namely using the rules of Islamic law in online business practices during the covid 19 pandemic. The results show that Islamic law has regulated ideal business communication and good, by applying the basic principles of Qaulan adidan (true words), Qaulan balighan (effective and on target), Qaulan ma'rufa (kind words), Qaulan mansura (easy words), Qaulan layyina (weak words gentle), Qaulan karimah (noble words). The expected positive impact in this study is that every e-commers must provide online and communicative services to consumers, taking into account the needs proposed by consumers, especially those who have limited the covid 19 pandemic.